High-tolerance PMP hollow fiber degassing membrane as well as preparation method and application thereof

By using PMP materials and melt stretching method to prepare hollow fiber degassing films, the crystallinity and crystal form ratio are improved, and the tolerance and efficiency of existing films in complex solvent systems are solved, achieving high efficiency and durability The degassing effect avoids the risk of ban on PTFE membrane.

CN119425410APending Publication Date: 2025-02-14HANGZHOU COBETTER FILTRATION EQUIPMENT CO LTD

Patent Information

Application Number
CN202410322597.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-20
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When facing complex solvent systems such as ceramic ink and UV ink, the existing hollow fiber degassing film has poor tolerance and short service life. Although the PTFE degassing film has good tolerance, the degassing efficiency is low, and it exists in the EU. The ban threatens.

Method used

The hollow fiber degassing film is prepared by using PMP materials. The preparation is made by melt stretching method to improve the XRD crystallinity and I crystal form ratio of the film, and combine the appropriate thickness and O2 permeability rate to ensure the film's tolerance and degassing efficiency.

Benefits of technology

A degassing film with extremely high tolerance and high degassing efficiency in complex solvent systems is achieved, avoiding the inefficiency and prohibition risks of PTFE film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425410A_ABST
    Figure CN119425410A_ABST
Patent Text Reader

Abstract

The invention relates to a high-tolerance PMP hollow fiber degassing membrane and a preparation method and application thereof.The high-tolerance PMP hollow fiber degassing membrane comprises a body, one side of the body is an inner surface facing an inner cavity, the other side of the body is an outer surface, a non-directional zigzag channel is formed in the body, and the thickness of the degassing membrane is 10-50 microns; the O2 permeation rate of the degassing membrane is 10 to 100 ml / (min.bar.m < 2 >); the XRD crystallinity of the degassing film is not lower than 60%; the degassing film contains a crystal form I belonging to a tetragonal crystal system, wherein the crystal form I accounts for 60-98.5% of the whole crystal form; under the action that the air inlet pressure is 0.5 MPa, an isobutanol solution containing methyl orange serves as a standard solution to fill the outer surface of the hollow fiber degassing membrane, breakthrough time testing is conducted on the hollow fiber degassing membrane, and the breakthrough time of the hollow fiber degassing membrane is larger than 60 min. The degassing membrane disclosed by the invention is mainly suitable for being applied to the field of liquid systems with certain corrosivity and relatively active chemical properties, such as ceramic ink, UV ink and the like, and has the advantages of extreme tolerance, good degassing rate and relatively high degassing efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of membrane materials, in particular to a high-tolerance PMP hollow fiber degassing membrane and a preparation method and application thereof. Background Art

[0002] Degassing refers to the process of removing gas from liquid or solid. Currently, the commonly used degassing methods include vacuum degassing, membrane degassing, dissolution degassing and gas displacement degassing. Membrane degassing uses the selective permeability of special membrane materials to separate gases (such as oxygen, carbon dioxide, nitrogen and ammonia, etc.) from liquid or solid. Hollow fiber membrane refers to a membrane filament with a fiber-like appearance, self-supporting function and hollow inner cavity. Compared with other separation membranes (such as flat membranes), due to the smaller diameter of hollow fiber membranes, they can be closely arranged in the device, thus having a larger unit volume packing density and providing a larger surface area (for gas exchange). Therefore, hollow fiber membranes are widely used in various degassing fields such as ultrapure water degassing, ink degassing, etc.

[0003] At present, there are various hollow fiber degassing membranes on the market. For example, the U.S. Patent No. US4055696A on porous polypropylene hollow filaments and preparation methods thereof (applied by Mitsubishi Rayon Co., Ltd.) discloses a hollow fiber degassing membrane made of PP material, which has good degassing rate and degassing efficiency. However, since the properties of PP material are relatively active and its surface energy is relatively high, when encountering some complex solvent systems such as ceramic ink, UV ink and other liquid systems containing certain corrosiveness and relatively active chemical properties (for example, ceramic ink may contain ceramic pigments, solvents, dispersants, adhesives, surfactants and leveling agents, defoamers, etc., and its liquid system components are relatively complex and have certain corrosiveness and chemical activity), the hollow fiber degassing membrane made of PP material may be easily broken by such liquid systems containing corrosiveness and relatively active chemical properties as ceramic ink, UV ink, etc., which is reflected in the poor tolerance and short service life of the hollow fiber degassing membrane.

[0004] Polytetrafluoroethylene, commonly known as the "king of plastics", has very stable chemical properties and is resistant to acids, alkalis, and various organic solvents. PTFE degassing membranes are also often used in the degassing of liquid systems such as the above-mentioned ceramic inks and UV inks that contain certain corrosiveness and relatively active chemical properties; for example, in the production of high-purity chemicals, PTFE degassing membranes can be used to remove impurities and harmful substances in the gas, thereby improving the purity and quality of the product; for example, in semiconductor manufacturing, PTFE degassing membranes can be used to prevent acidic gases from corroding production equipment, thereby improving production efficiency and product quality; such as the publication number CN106045175A-Ammonia nitrogen wastewater treatment system based on PTFE deamination membrane components and its process (Applied by Suzhou New Energy Environmental Technology Co., Ltd.) uses PTFE degassing membrane to remove ammonia and nitrogen from wastewater; and in order to ensure that the PTFE membrane filament has a long service life in these "harsh" environments, the overall porosity of the PTFE degassing membrane is relatively low, and the inner and outer surfaces are very dense. In addition, due to its own material properties, the overall degassing rate of the membrane filament is not high, and the degassing efficiency is increasingly unable to meet the needs of practical applications; at the same time, there is a risk of PTFE degassing membrane being banned, so R&D personnel are actively developing a degassing membrane with extremely strong tolerance and good degassing efficiency, and suitable for degassing applications in liquid systems such as ceramic inks and UV inks that have certain corrosiveness and relatively active chemical properties. Summary of the invention

[0005] The purpose of the present invention is to provide a highly tolerant PMP hollow fiber degassing membrane and a preparation method and application thereof. The degassing membrane has a high XRD crystallinity and a proportion of type I crystal, and is combined with a certain thickness and a certain degassing rate to obtain a degassing membrane with extremely strong tolerance and good degassing efficiency, and is suitable for degassing applications in liquid systems with certain corrosiveness and active chemical properties such as ceramic inks and UV inks.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A high-tolerance PMP hollow fiber degassing membrane comprises a main body, one side of the main body is an inner surface facing an inner cavity, the other side of the main body is an outer surface, and the main body has a non-directional tortuous channel.

[0008] The thickness of the degassing film is 10-50 μm;

[0009] The O2 permeation rate of the degassing membrane is 10-100 ml / (min·bar·m 2 );

[0010] The XRD crystallinity of the degassing film is not less than 60%;

[0011] The degassing film contains crystal form I belonging to the tetragonal system, wherein the content of crystal form I accounts for 60%-98.5% of the overall crystal form;

[0012] Under the action of an inlet pressure of 0.5 MPa, an isobutyl alcohol solution containing methyl orange was used as a standard solution to fill the outer surface of the hollow fiber degassing membrane, and a breakthrough time test was performed on the hollow fiber degassing membrane. The breakthrough time of the hollow fiber degassing membrane was greater than 60 min.

[0013] As is known to all, in the field of degassing applications, the tolerance of the degassing membrane is mainly reflected in the properties of the degassing membrane material itself, the structure related to the outer surface of the degassing membrane and the overall density of the degassing membrane. Therefore, under normal circumstances, in some degassing applications of solution systems with certain corrosiveness and active chemical properties, such as ceramic ink degassing, UV ink degassing, PI glue degassing in photoresist, etc., in order to consider that the degassing membrane has better tolerance as a whole, the technicians in this field usually select a degassing membrane material with relatively stable properties, and also make the outer surface of the degassing membrane and the degassing membrane as a whole relatively dense. The degassing membrane with such a structure (i.e., the degassing membrane) The outer surface and the whole of the air membrane are relatively dense), which is often accompanied by the sacrifice of degassing rate and degassing efficiency, and usually has a relatively low degassing rate and degassing efficiency; for example, in order to meet the degassing work in the above-mentioned technical field, technical personnel in the field use PTFE, which has stable chemical properties and good acid, alkali and solvent resistance, and is often used to prepare a degassing membrane with excellent tolerance. However, PTFE has a relatively low degassing efficiency. At the same time, with the EU's control ban on perfluoro and polyfluoroalkyl compounds (PFAS), how to obtain a degassing membrane with tolerance comparable to that of PTFE membrane has become a hot topic for research and development personnel. PMP is a semi-crystalline polymer that has good selective permeability to O2, that is, it has good oxygen permeability. At the same time, the properties of PMP materials are relatively stable, and it has good tolerance to solution systems with certain corrosiveness and chemically active properties such as ceramic inks and UV inks. Therefore, PMP is usually used to prepare gas separation membranes and has become a goal of continuous research and development by researchers.

[0014] The melt stretching method is a molding method in which a polymer material is melted and extruded, and then the extruded film or sheet is unidirectionally or bidirectionally stretched to form micropores or cracks on the obtained film. Compared with the phase separation method, the melt stretching method does not require additives (such as solvents, non-solvents, etc.), and only has one polymer raw material. Therefore, it can better avoid the problem of contamination of the degassing liquid due to the introduction of additives during the application of the degassing membrane; in the present invention, the PMP degassing membrane is prepared by the melt stretching method. Under normal circumstances, those skilled in the art generally believe that the degassing membrane prepared by the melt stretching method is When making a degassing membrane, the higher the crystallinity of the membrane, the higher the porosity of the final degassing membrane, forming more pore structures (more crystal nuclei are pulled apart to form pore structures), and the tolerance of the degassing membrane will be greatly reduced; and in order to ensure the tolerance of the degassing membrane, it is necessary to reduce the XRD crystallinity of the membrane as much as possible (for example, reduce the crystallinity of the raw material), so that the porosity of the final degassing membrane is low and the membrane is relatively dense as a whole; thereby ensuring that the degassing membrane can be better applied in the above-mentioned degassing field of liquid systems with certain corrosiveness and active chemical properties or liquid systems with strong permeability. At the same time, we found that the consequence of such a degassing membrane structure is that the degassing rate and degassing efficiency of the degassing membrane are greatly sacrificed, which greatly affects the production efficiency.

[0015] As one of the inventivenesses of the present invention, the crystallinity of the PMP degassing membrane of the present invention is not the lower the better, on the contrary, the crystallinity of the degassing membrane of the present invention has a relatively high value (the XRD crystallinity of the degassing membrane of the present invention is not less than 60%), because in the PMP degassing membrane, the molecular arrangement of the crystalline region is more regular and orderly than that of the amorphous region, so that the crystalline region has better chemical stability, which is conducive to giving the degassing membrane better tolerance; at the same time, the degassing membrane contains the I crystal type belonging to the tetragonal crystal system, wherein the I crystal type accounts for 60%-98.5% of the overall crystal type, that is, a large amount of I crystal type is formed in the degassing membrane, and the I crystal type is more stable in structure than other crystal types, which can further improve the tolerance of the membrane; further, the degassing membrane of the present invention has a suitable O2 permeation rate (10-100ml / (min·bar·m 2), the size of the oxygen permeation rate reflects the overall structure of the membrane, indicating that the membrane is relatively dense as a whole, and at the same time, with the synergistic effect of appropriate thickness, it further ensures that the membrane as a whole has high tolerance; finally, the degassing membrane is guaranteed to be under the action of an inlet pressure of 0.5MPa, and an isobutanol solution containing methyl orange is used as a standard solution for tolerance testing. The breakthrough time of the degassing membrane is greater than 60min, which not only reflects the overall structure of the membrane (for example, it reflects that the membrane is relatively dense as a whole, especially the outer surface of the membrane is also relatively dense, and the porosity of the outer surface of the degassing membrane will greatly affect the tolerance of the degassing membrane), but also shows that under the combined effect of these characteristics, the degassing membrane also has extreme tolerance, truly replacing the PTFE degassing membrane, and is suitable for use in various liquid systems with certain corrosiveness and active chemical properties, such as ceramic inks and UV inks. That is to say, when the crystallinity of the degassing membrane is maintained at a high level (XRD crystallinity is not less than 60%), the tolerance of the degassing membrane does not drop as expected and become unusable. Instead, the combination of other characteristics ensures that the degassing membrane has extreme tolerance. This is different from the existing relevant cognition, and truly overcomes the technical bias in the relevant cognition, which is creative.

[0016] Furthermore, it is generally believed that the tolerance and degassing rate of the degassing membrane are relatively negatively correlated, that is, the better the tolerance of the degassing membrane, the lower the degassing efficiency of the membrane. For example, although the PTFE degassing membrane has good tolerance, the degassing efficiency is very low (the deoxidation efficiency is often only about 10%). Such degassing efficiency is increasingly unable to meet the needs of practical applications. In the present invention, the membrane material is PMP, and the XRD crystallinity and the proportion of the I crystal form are combined with the appropriate thickness of the degassing membrane and the appropriate deoxidation rate. The degassing membrane has excellent tolerance and high degassing efficiency. This is because PMP There are usually four crystal forms, namely, crystal form I, crystal form II, crystal form III and crystal form IV, among which crystal forms I and III belong to the tetragonal system, crystal form II belongs to the monoclinic system, and crystal form IV belongs to the hexagonal system; among them, crystal form I is the most stable tetragonal crystal form, and the density constant of PMP polymer with crystal form I is lower than the density constant of PMP polymer with other crystal forms; under normal circumstances, the density of the crystal region of the most stable crystal form I is lower than the density of the amorphous region at room temperature, so that the crystalline phase of PMP is permeable, and the molecular chain arrangement of the PMP polymer with crystal form I is relatively loose, which is conducive to the penetration of gas molecules. In other words, when the proportion of crystal form I in the PMP polymer is relatively higher, the molecular chain arrangement of the PMP polymer is relatively loose, and its crystal region density is lower than that of the amorphous region. In addition, the PMP material itself has good selective permeability to O2, which then gives such a PMP degassing membrane good gas permeability. Therefore, although the overall structure of the degassing membrane of the present invention is relatively dense, the relatively high XRD crystallinity and the appropriate proportion of type I crystal make the degassing membrane have appropriate lattice spacing, appropriate molecular chain arrangement and crystal area density, so that the gas to be removed can penetrate through the gaps between the lattices. In addition, the PMP material itself has good selective permeability to O2. Combined with the degassing membrane having an appropriate thickness (10-50μm) and a certain O2 permeation rate, the degassing membrane is guaranteed to have a high degassing efficiency, basically replacing the PTFE degassing membrane, and is suitable for use in the degassing field of liquid systems with certain corrosiveness and active chemical properties or liquid systems with strong permeability. The degassing membrane of the present invention has a higher degassing efficiency (compared with the PTFE degassing membrane), and at the same time overcomes the problem that the tolerance and degassing efficiency of the degassing membrane in the related art cannot be achieved at the same time, and is further creative.

[0017] In addition, we found that when the crystallinity of the degassing membrane is at a relatively high level (XRD crystallinity is not less than 60%), the mechanical strength of the degassing membrane is also maintained at a relatively good level. After long-term erosion by liquid systems with certain corrosive and chemically active properties or liquid systems with strong permeability, the various properties of the degassing membrane can still remain relatively stable.

[0018] The non-directional tortuous pathways in the present invention refer to randomly oriented groove structures and / or discretely distributed pore structures, and the non-directional tortuous pathways are interconnected; and the fibers forming the porous structure of the membrane are continuous. It can be understood that "continuous" means that basically all the fibers are interconnected as a whole and are formed as a whole without the use of additional adhesives to connect them to each other. Unless torn by external force, the network-like fibers cannot be separated from each other, that is, the porous membrane of the present invention is a single-layer membrane structure, not a composite membrane structure.

[0019] The thickness of the hollow fiber membrane in the present invention can be measured by computer software (such as Matlab, NIS-Elements, etc.) or manually after characterizing the cross-section of the hollow fiber membrane using a SEM electron microscope, and then performing corresponding calculations to obtain the thickness of the hollow fiber membrane.

[0020] The oxygen permeation rate of the present invention is to subject one side of the membrane sample to the gas to be tested (oxygen) under the conditions of a temperature of 25°C, a pressure of 0.1 bar, and a membrane sample area of ​​0.1 square meters; supply the gas to be tested (oxygen) into the inner cavity of the hollow fiber membrane; use a flow meter (Japan KOFLOC / 4800) to measure the volume flow rate of the gas passing through the sample membrane wall; test from the inside of the membrane to the outside of the membrane three times, and from the outside of the membrane to the inside of the membrane three times, and then take the average value, which is the oxygen permeation rate of the membrane. The unit of oxygen permeation rate is ml / (min·bar·m 2 ); The oxygen permeation rate can represent the overall porosity and density of the membrane to a certain extent. Generally speaking (when the thickness is almost the same), the lower the oxygen permeation rate, the smaller the overall pores of the membrane and the denser the structure; the higher the oxygen permeation rate, the larger the overall pores of the membrane and the looser the structure; therefore, the thickness and the oxygen permeation rate can basically reflect the overall density of the membrane in coordination.

[0021] The XRD crystallinity of the degassed film refers to obtaining the XRD diffraction pattern of the degassed film by X-ray diffraction and calculating the diffraction peak area representing the crystalline form and the sum of the diffraction peak area representing the crystalline form and the diffraction peak area of ​​the amorphous form respectively. The XRD crystallinity value of the degassed film is obtained by the diffraction peak area of ​​the crystalline form: the sum of the diffraction peak area of ​​the crystalline form and the diffraction peak area of ​​the amorphous form.

[0022] The original image data of the degassed film can be obtained by X-ray diffraction, and after peak fitting and processing using software such as Jade, a coordinate diagram of the 2θ angle and the diffraction peak intensity can be obtained, wherein the diffraction peaks at 2θ angles of around 9.5°, 13.4°, 16.6°, 18.3°, 20.7° and 21.3° represent the diffraction peaks of the I crystal form, and the proportion of the I crystal form in the overall crystal form can be obtained by calculating the sum of the diffraction peak intensities at 2θ angles of around 9.5°, 13.4°, 16.6°, 18.3°, 20.7° and 21.3° (that is, the former), and then calculating the intensities of all the crystal diffraction peaks (that is, the latter), and then the proportion of the I crystal form in the overall crystal form can be obtained by the former / latter.

[0023] Furthermore, the thickness of the degassing membrane is 12-45 μm; the gap area ratio of the outer surface is not higher than 2%; the gap area ratio of the inner surface is not higher than 10%, and the gap area ratio of the inner surface is greater than the gap area ratio of the outer surface;

[0024] The O2 permeation rate of the degassing membrane is 20-90 ml / (min·bar·m 2 );

[0025] The XRD crystallinity of the degassing film is 70%-90%.

[0026] The degassing membrane of the present invention has a suitable thickness (12-45 μm) and a suitable O2 permeation rate (20-90 ml / (min·bar·m 2)), combined with the relatively high XRD crystallinity (70%-90%) of the degassing membrane, the degassing membrane can be given extreme tolerance. On the basis of the above, the outer surface (the gap area ratio is not higher than 2%, the outer surface is relatively dense, there are no gaps or only a small number of cracks) and the inner surface (the gap area ratio is not higher than 10%, and there are preferably a small number of cracks on the inner surface) of the degassing membrane are controlled to have a suitable surface structure. We are pleasantly surprised to find that the degassing membrane is still relatively excellent in tolerance when used in the degassing field of liquid systems with certain corrosiveness and chemically active properties or liquid systems with strong permeability, and the degassing efficiency of the degassing membrane can be significantly improved, that is, the degassing membrane has excellent tolerance while further having a suitable degassing rate and a high degassing efficiency. This may be because, on the one hand, the outer surface is where the degassing membrane is in direct contact with the liquid system. The combined effect of the PMP material and the relatively dense outer surface is conducive to ensuring the overall tolerance of the membrane. When the inner surface has a certain gap area ratio, when the gas to be removed (such as oxygen) can be breathed through the gaps on the inner surface, the efficiency of the gas to be removed in the degassing membrane is greatly and effectively improved, and degassing in multiple ways is truly realized, efficient degassing, and the impact of gases such as oxygen on practical applications is reduced, so that it can better replace PTFE membrane and be applied in the above-mentioned fields.

[0027] On the other hand, we found that if we pursue the ultimate tolerance of PMP degassing membrane in the above-mentioned fields, that is, make the inner and outer surfaces of the PMP degassing membrane dense, the PMP degassing membrane filaments are prone to breakage during and after the preparation due to the relatively poor toughness of the PMP material itself; we unexpectedly found that by having a certain gap area ratio on the inner surface, the toughness of the PMP degassing membrane can be improved to a certain extent, which can effectively reduce the probability of PMP degassing membrane filament breakage.

[0028] In addition, we found that when the XRD crystallinity of the degassing membrane is controlled within the range of 70%-90%, the mechanical strength of the degassing membrane is also relatively good. After being subjected to long-term erosion by liquid systems with certain corrosive and chemically active properties or liquid systems with strong permeability, the various properties of the degassing membrane can still remain relatively stable.

[0029] The characteristics of the degassing membrane of the present invention, such as the gap area ratio, can be characterized by using a scanning electron microscope to characterize the morphology of the membrane structure, and then using computer software (such as Matlab, NIS-Elements, etc.) or manually to measure and perform corresponding calculations; in the preparation process of the membrane, in the direction perpendicular to the membrane thickness (if the membrane is in the form of a flat membrane, this direction is the plane direction; if the membrane is in the form of a hollow fiber membrane, this direction is perpendicular to the radial direction), the size of its various characteristic cracks and the distribution of the cracks are roughly uniform and basically consistent; so the size of the gap area ratio of a partial area on the corresponding plane can be used to reflect the size of the gap area ratio on the plane; when actually measuring, the inner and outer surfaces of the membrane filament can be characterized by an electron microscope to obtain the corresponding SEM image, and since the size of the cracks (gaps) on the inner and outer surfaces of the membrane and the distribution of the cracks (gaps) are roughly uniform, a certain area can be selected, for example 1μm 2 (1μm times 1μm) or 100μm 2 (10μm multiplied by 10μm) or, the specific area size depends on the actual situation, and then use the corresponding computer software or manually measure the size of the gap area ratio on the area, conduct several tests, and take the average value to obtain the gap area ratio on the inner and outer surfaces of the membrane; of course, technical personnel in this field can also obtain the above parameters through other measurement methods, and the above measurement methods are for reference only).

[0030] Furthermore, the diffraction peak intensity of the degassing film near 9.48° at 2θ in the XRD diffraction spectrum accounts for 60%-90% of the overall crystal diffraction peak intensity, the half-peak width of the diffraction peak near 9.48° at 2θ is 0.1°-0.5°, and the grain size is not less than 200 angstroms.

[0031] The present invention tests the degassing film by the XRD method and obtains the X-ray diffraction spectrum of the degassing film. In the X-ray diffraction spectrum, the diffraction peak located near the 2θ angle of 9.5° is one of the characteristic diffraction peaks used to characterize the I crystal form, which can usually represent the 200 crystal plane. The proportion of the diffraction peak intensity located near the 2θ angle of 9.5° to the overall crystal diffraction peak intensity can characterize the proportion of the I crystal form in the degassing film to a certain extent. The I crystal form of PMP belongs to the most stable tetragonal system, and its crystal form morphology has good stability; at the same time, the crystal form I is relatively smaller than other crystal forms (II, III, IV crystal forms, wherein II belongs to the monoclinic system, III belongs to the tetragonal system, and IV belongs to the hexagonal system). The density of the crystal region is lower than the density of the amorphous region under room temperature conditions. Therefore, under such a crystal system, the performance of the crystalline phase of PMP in permeating gas is relatively better. That is to say, the higher the proportion of crystal form I in the crystal form, the lower the density of the PMP crystal region will be than that of the amorphous region, so that when the degassing film is relatively dense, the PMP degassing film can still be better permeable through the gaps between the lattices, ensuring that the degassing film has a high degassing efficiency. Through the analysis of the X-ray diffraction spectrum, we found that the normalized integrated intensity of the diffraction peak located near the 2θ angle of 9.5° accounts for the highest proportion, that is, the diffraction peak located near the 2θ angle of 9.5° contributes the most to the crystal crystallinity, and the crystalline diffraction peak is one of the characteristic diffraction peaks used to characterize the crystal form I, that is, the proportion of the diffraction peak intensity located near the 2θ angle of 9.5° to the overall crystalline diffraction peak intensity can be used to roughly characterize the proportion of crystal form I in the crystalline region of the degassing film; therefore, the appropriate proportion (60%-90%) of the diffraction peak intensity located near the 2θ angle of 9.5° to the overall crystalline diffraction peak intensity can effectively ensure the permeability of the crystalline region of the PMP degassing film.

[0032] Half-peak width refers to the half-peak width of each diffraction peak in the X-ray diffraction spectrum, usually expressed as an angle or 2θ value. Half-peak width can be used to measure the change in lattice parameters in the crystal structure. Generally speaking, the smaller the half-peak width of the diffraction peak, the more orderly the arrangement of atoms in the crystal and the fewer crystal defects; the larger the half-peak width, the more disordered the arrangement of atoms in the crystal and the more crystal defects. Therefore, the half-peak width in the X-ray diffraction spectrum can be used to evaluate the quality and degree of defects of the crystal. The half-peak width of the diffraction peak at a 2θ angle of 9.5° in the present invention is within a suitable numerical range (0.1°-0.5°), and the grain size is not less than 200 angstroms, which means that the more ordered the atomic arrangement in the degassing membrane crystal of the present invention is, the fewer the crystal defects are, and then when the degassing membrane is applied to the degassing field of a liquid system with certain corrosiveness and chemically active properties or a liquid system with strong permeability, the gas to be degassed can be better degassed through the gaps between the lattices, so that the degassing membrane has extreme long-term tolerance, and also gives the degassing membrane good mechanical strength. The mechanical strength of the degassing membrane is also maintained at a relatively good level. After the degassing membrane is subjected to long-term erosion by a liquid system with certain corrosiveness and chemically active properties or a liquid system with strong permeability, the various properties of the degassing membrane can still remain in a relatively stable state.

[0033] The "near" in the diffraction peak near 9.5° at a 2θ angle of the present invention specifically refers to a point value within an upper and lower fluctuation range of 0.2°. For example, the "diffraction peak near 9.5°" refers to a diffraction peak in the range of 9.3° to 9.7°.

[0034] Furthermore, the inner surface has a plurality of first cracks in the form of silver streaks, and the average SEM width of the first cracks is 0.1-20 nm;

[0035] The content of the Form I crystal accounts for 70%-98% of the overall crystal form.

[0036] The degassing membrane of the present invention has a first crack with a suitable SEM width (0.1-20nm) on the inner surface, so that the degassing membrane still has extreme tolerance when used in the degassing field of liquid systems with certain corrosiveness and chemically active properties or liquid systems with strong permeability, and can also significantly improve the degassing efficiency of the degassing membrane; in addition, when the content of type I in the overall crystal form is relatively high (70%-98%), it means to a certain extent that the degassing membrane has a suitable ratio of crystalline and amorphous regions, so that the gas to be removed can also be better ventilated through the gaps between the lattices, and then under the joint action of the first crack with a suitable SEM width on the inner surface of the degassing membrane, the permeation rate of the gas to be removed is effectively improved, thereby giving the degassing membrane a good degassing rate and a high degassing efficiency.

[0037] On the other hand, when the inner and outer surfaces of the PMP degassing membrane are relatively dense, the PMP degassing membrane filaments are prone to breakage due to the poor toughness of the PMP material itself, making it difficult to process and produce well. We unexpectedly discovered that when the inner surface has a certain SEM average width of the first crack, the toughness of the PMP degassing membrane can be improved to a certain extent, which can effectively reduce the probability of PMP degassing membrane filament breakage.

[0038] Furthermore, a plurality of the first cracks are evenly distributed on the inner surface, the SEM average width of the first cracks is 1-18 nm, and the gap area ratio of the inner surface is 0.2%-8%.

[0039] When the first cracks of the degassing membrane of the present invention are uniformly distributed on the inner surface, and the SEM average width of the first cracks of the degassing membrane of the present invention is controlled within the range of 1-18nm and the gap area ratio of the inner surface is controlled within the range of 0.2%-8%, the tolerance of the degassing membrane is still relatively excellent. This may be because the average width of the first cracks on the inner surface (1-18nm) and the gap area ratio of the inner surface (0.2%-8%) are relatively small, thereby significantly increasing the degassing rate and improving the degassing efficiency while the tolerance of the degassing membrane is hardly affected. After research, it was found that compared with the unevenly distributed first cracks, the degassing membrane with evenly distributed first cracks has a relatively longer breakthrough time when used in the degassing field of liquid systems with certain corrosive and chemically active properties or liquid systems with strong permeability, that is, the tolerance of the degassing membrane is relatively better; the reason may be that when the first cracks are unevenly distributed on the inner surface (usually it means that the first cracks are concentrated in part of the inner surface), and the gap area ratio there is larger than that of other areas, when subjected to long-term erosion by liquid systems with certain corrosive and chemically active properties or liquid systems with strong permeability, the area where the cracks are concentrated may be more susceptible to erosion and cause the area to become a breakthrough point for liquid erosion, which in turn causes the breakthrough time of the degassing membrane after long-term degassing to be not as good as the breakthrough time of the degassing membrane with the first cracks evenly distributed on the inner surface.

[0040] At the same time, we found that when the first cracks are evenly distributed on the inner surface, the degassing rate and degassing efficiency of the degassing membrane can be effectively improved, and the toughness of the degassing membrane can also be improved to a certain extent. As a result, when the degassing membrane is used in the degassing field of liquid systems with certain corrosive and chemically active properties or liquid systems with strong permeability, it not only has extreme tolerance, but also has a good degassing rate and high degassing efficiency. At the same time, it can improve the problem of insufficient toughness of PMP degassing membrane fibers, so that the PMP degassing membrane fibers have good tensile strength and elongation at break.

[0041] The uniformly distributed first cracks in the present invention specifically refer to multiple observations of the inner surface of the degassing membrane through a SEM electron microscope, where it can be clearly observed that there is basically no relatively dense area on the inner surface of the degassing membrane, and the first cracks are basically uniformly distributed on the inner surface.

[0042] Furthermore, the inner surface has an inner crack zone and an inner dense zone, the inner dense zone is a dense area, a number of the first cracks are located in the inner crack zone, and the SEM average width of the first cracks is 0.5-15nm, and the gap area rate of the inner crack zone is 0.5%-9%.

[0043] When the first cracks of the degassing membrane of the present invention are unevenly distributed on the inner surface, that is, there are inner dense areas and inner crack areas, combined with the degassing membrane having a suitable SEM average width of the first crack (0.5-15nm) and the gap area ratio of the inner crack area (0.5%-9%), the degassing membrane is given a suitable degassing rate and a higher degassing efficiency; at the same time, the toughness of the PMP degassing membrane is also improved, so that the degassing membrane filament has good tensile strength and elongation at break; after research, it was found that when the SEM average width of the first crack was controlled within the range of 0.5-15nm, and the gap area ratio of the inner crack area was controlled within the range of 0.5%-9%, the tolerance of the degassing membrane was almost unaffected, and it can still be well applied to the degassing field of liquid systems with certain corrosiveness and active chemical properties or liquid systems with strong permeability, and has excellent tolerance.

[0044] The inner dense area in the present invention specifically refers to an inner dense area where no crack structure can be observed or only a very small number of cracks can be observed when photographed by a scanning electron microscope at 50,000 times.

[0045] Furthermore, the inner surface has a plurality of inner degassing pores, the SEM average pore size of the inner degassing pores is greater than the SEM average width of the first cracks, the SEM average pore size of the inner degassing pores is 1-40 nm, and the thickness of the degassing film is 18-48 μm.

[0046] When there are a number of internal degassing pores and first cracks on the inner surface of the degassing membrane of the present invention, combined with the SEM average pore size of the internal degassing pores being controlled at 1-40nm and the thickness of the degassing membrane being controlled at 18-48μm, we are pleasantly surprised to find that although the inner surface of the degassing membrane has a certain number of internal degassing pores, the SEM average pore size of the internal degassing pores is still relatively small. In addition, under the appropriate thickness of the degassing membrane, the degassing membrane is guaranteed to have a suitable non-directional tortuous path, and the tolerance of the degassing membrane is still relatively excellent; at the same time, compared with the first cracks, the internal degassing pores have better gas permeability, so that the degassing membrane can have a better gas permeation rate, and then can significantly improve the degassing rate and degassing efficiency of the degassing membrane; in addition, we unexpectedly found that when the inner surface of the degassing membrane has a certain number and size of internal degassing pores and first cracks, the toughness of the degassing membrane can also be relatively better improved, and the tensile strength and elongation at break of the degassing membrane can be well improved.

[0047] If the SEM average pore size of the internal degassing pores is too small, the difference between the internal degassing pores and the first cracks may be small, and the existence of the internal degassing pores cannot play a role in better improving the rate at which the gas to be removed penetrates through the inner surface of the degassing membrane; if the SEM average pore size of the internal degassing pores is too large, the compressive strength of the inner surface of the degassing membrane and the stability during degassing may be affected and reduced after long-term erosion by a liquid system with certain corrosiveness and chemically active properties or a liquid system with strong permeability.

[0048] The internal degassing pores in the present invention may have two morphologies when observed through SEM electron microscope, one is a relatively regular circular hole, and the other is an elliptical hole. The SEM average pore size of the internal degassing pores claimed in the present invention specifically refers to the diameter length of the relatively regular circular hole and the length in the short diameter direction of the elliptical hole.

[0049] Furthermore, the density of the inner degassing pores is not greater than 20 / 1 μm. 2 , the ratio of the SEM average pore size of the inner degassing pores to the SEM average width of the first cracks is 1.5-15.

[0050] When the density of the internal degassing pores of the present invention is not greater than 20 / 1 μm 2When the ratio of the SEM average pore size of the internal degassing pores to the SEM average width of the first cracks is controlled at an appropriate ratio (1.5-15), although there are internal degassing pores on the inner surface, the distribution of the internal degassing pores on the inner surface is still relatively sparse, thereby ensuring that the degassing membrane as a whole still has excellent tolerance while being able to give the degassing membrane a higher degassing efficiency; at the same time, under the joint action of such a number and size of internal degassing pores and the first cracks, the overall toughness of the degassing membrane can also be greatly improved, which is specifically reflected in the tensile strength, elongation at break, etc. can also be well improved.

[0051] In addition, the ratio of the pore size of the inner degassing pores to the SEM average width of the first cracks reflects the differentiation between the inner degassing pores and the first cracks to a certain extent, so that the inner degassing pores can better improve the degassing efficiency of the degassing membrane while ensuring that the degassing membrane has excellent tolerance; if the ratio of the pore size of the inner degassing pores to the SEM average width of the first cracks is too high, it means that the pore size of the inner degassing pores is too large compared to the first cracks, which may cause the inner degassing pores to be subjected to a certain degree of influence on the degassing stability and compressive strength of the inner surface after being eroded for a long time by a liquid system with certain corrosive and chemically active properties or a liquid system with strong permeability during the degassing process; if the ratio of the pore size of the inner degassing pores to the SEM average width of the first cracks is too small, the difference between the inner degassing pores and the first cracks is not obvious, so that the inner degassing pores cannot play a good role in improving the degassing efficiency, and the toughening effect on the degassing membrane filaments is relatively limited.

[0052] Furthermore, the outer surface has a plurality of second cracks, the SEM average width of the second cracks is no more than 20 nm, and the ratio of the SEM average width of the second cracks to the SEM average width of the first cracks is 0.2-0.9.

[0053] When the outer surface of the present invention has a second crack, by controlling the second crack to be within a suitable SEM average width (not greater than 20 nm), and the ratio of the SEM average width of the second crack to the SEM average width of the first crack is controlled within a suitable range (0.2-0.9), we found that the degassing rate and degassing efficiency of the degassing membrane are significantly improved, and the degassing membrane still has excellent tolerance; this may be because the PMP material has good tolerance to liquid systems with certain corrosive and chemically active properties or liquid systems with strong permeability, and at the same time, combined with the relatively high crystallinity of the degassing membrane (XRD crystallinity is not less than 60%), although the outer surface has a second crack, the degassing membrane as a whole is applied to liquid systems with certain corrosive and chemical properties. In the field of degassing of liquid systems with active chemical properties or liquid systems with strong permeability, the tolerance of the degassing membrane is still relatively excellent; in addition, the ratio of the SEM average width of the second crack to the first crack is controlled within an appropriate range, reflecting that the SEM average width of the second crack on the outer surface is smaller than the SEM average width of the first crack on the inner surface. This is because the outer surface, as the side in direct contact with the liquid to be degassed, needs to have better tolerance than the inner surface. Therefore, even when the second crack needs to be opened on the outer surface of the degassing membrane to improve the degassing rate and degassing efficiency of the degassing membrane, the width of the second crack on the outer surface cannot be too large, thereby ensuring that the degassing membrane has a suitable degassing rate and a high degassing efficiency, while the tolerance of the degassing membrane is hardly affected.

[0054] Further, the infrared absorption spectra of the inner and outer surfaces of the degassing film are tested by ATR method, and the orientation coefficient X of the degassing film is calculated;

[0055] X=ABS 918 / ABS 1465 ;

[0056] ABS 918 For degassing membrane, the wave number is 918 cm -1 The absorption intensity in the vicinity;

[0057] ABS 1465 For degassing membrane, the wave number is 1465cm -1 The absorption intensity in the vicinity;

[0058] The external surface orientation coefficient X 外 =ABS 外表面918 / ABS 外表面1465 ;

[0059] Where X 外 The value range is 0.005-0.18;

[0060] ABS 外表面918The outer surface of the degassing membrane is at a wave number of 918 cm -1 The absorption intensity in the vicinity;

[0061] ABS 外表面1465 The outer surface of the degassing membrane at a wave number of 1465 cm -1 The absorption intensity near

[0062] The present invention selects a degassing membrane to perform infrared spectrum testing using a Fourier infrared spectrometer, including but not limited to, and controls the test pressure, selects the area of ​​the degassing membrane test and other factors to be consistent. In the infrared spectrum obtained by the test, after error elimination processing (such as baseline calibration, etc.), the wave number is 918cm -1 The absorption intensity near the peak area is used to characterize the absorption intensity, which is more accurate and objective. The orientation degree refers to the degree of orderly arrangement of macromolecular chains or segments in a specific direction in the crystal region. Within a certain range, the orientation degree determines and affects the crystallization performance of the degassing membrane. The wave number used in the present invention is 1465cm -1 The absorption intensity (peak area) near is taken as the standard peak, which is due to the wave number of 1465cm -1 The peak near the wave number is the bending vibration peak used to characterize the CH structure, and its value changes little. Finally, after research, it was determined that the wave number was 918cm -1 The absorption intensity (peak area) near the wave number is 1465cm -1 The ratio of the absorption intensity (peak area) near the inner and outer surfaces is used to reflect the degree of crystallization on different surfaces of the degassing film, that is, the orientation coefficient on the inner and outer surfaces.

[0063] The orientation coefficient of the outer surface of the degassing membrane of the present invention is controlled within the range of 0.005-0.18, which reflects that the orientation degree of the outer surface of the degassing membrane is at a good level, and then reflects that the crystallization degree of the outer surface is good (that is, the outer surface has a relatively suitable distribution of crystalline and amorphous regions). Therefore, even when the outer surface is relatively dense, due to the good crystallinity of the outer surface (suitable distribution of crystalline and amorphous regions), the degassing membrane can still pass through the gaps between the lattices to pass through the gas to be removed during degassing, and the crystal region can better block the infiltration and erosion of ceramic ink and UV ink, so that the PMP degassing membrane has a high degassing efficiency and excellent tolerance. At the same time, under the combined effect of such an outer surface orientation coefficient and the XRD crystallinity of the overall degassing membrane being relatively high, after the degassing membrane has been subjected to the erosion of a liquid system with certain corrosiveness and chemically active properties or a liquid system with strong permeability for a long time, the outer surface of the degassing membrane can still better block the liquid to be degassed, and the various properties of the degassing membrane can still be relatively stable.

[0064] Further, the inner surface orientation coefficient X 内=ABS 内表面918 / ABS 内表面1465 ;

[0065] Where X 内 The value range is 0.01-0.2; and X 内 :X 外 Meets 1.01-5;

[0066] ABS 内表面918 The outer surface of the degassing membrane is at a wave number of 918 cm -1 The absorption intensity in the vicinity;

[0067] ABS 内表面1465 The outer surface of the degassing membrane at a wave number of 1465 cm -1 The absorption intensity near

[0068] The orientation coefficient of the inner surface can also reflect the orientation degree of the inner surface to a certain extent. 内 The value range is 0.01-0.2, combined with X 内 :X 外 When the ratio of 1.01-5 is satisfied (reflecting that the orientation coefficient of the inner surface is relatively higher than that of the outer surface), the degassing film is endowed with a higher degassing rate and better mechanical strength. In the present invention, the orientation coefficient of the inner surface of the degassing film is relatively higher than that of the outer surface. This is because the inner surface is the main surface for degassing. On the one hand, the degassing rate and degassing efficiency of the degassing film can be improved through the first crack of the inner surface; on the other hand, the inner surface has a relatively high orientation degree, which to a certain extent reflects that the inner surface has a relatively high crystallinity, and then to a certain extent reflects that the inner surface has a suitable distribution of crystalline and amorphous regions, and at the same time, the number and size of the gaps between the lattices are relatively suitable, so that the effect of achieving ventilation through the gaps between the inner surface lattices is better, so that the degassing film has a higher degassing efficiency under the joint action of the first crack and the inner surface orientation coefficient.

[0069] Furthermore, the tensile strength of the degassing film is not less than 150CN, and the elongation at break is 30-150%;

[0070] The deoxidation efficiency of the degassing membrane is 25%-70%.

[0071] The degassing membrane of the present invention has good tensile strength and elongation at break, and also has extremely high deoxidation efficiency, which can still reach 25%-70% when applied to the degassing field of liquid systems with certain corrosiveness and chemically active properties or liquid systems with strong permeability, and can well remove gases in liquid systems such as ceramic inks and UV inks.

[0072] The deoxygenation efficiency of the degassing membrane can be tested by the following test method: the degassing membrane of the present invention is used as a raw material, and the membrane area is 0.65m 2 The components are connected with the dissolved oxygen meter, water circuit and components for testing. The water circuit is used to transport the degassed liquid (such as active solutions such as ink / plating solution), the components are used to degas the degassed liquid, and the dissolved oxygen meter is used to detect the oxygen content of the degassed liquid after degassing. The degassed liquid is deionized water and the temperature of the degassed liquid is 25℃. The inside of the membrane is vacuum purged.

[0073] Step 1: Detect the initial oxygen content of the degassed liquid. Pump the degassed liquid into the water circuit. At this time, turn off the vacuum equipment to make the inner side of the membrane at normal pressure. The degassed liquid passes through the assembly (without degassing) and then passes through the dissolved oxygen meter. Keep the flow rate of the degassed liquid entering the dissolved oxygen meter at about 1.8 GLH. Observe the changes in the dissolved oxygen reading on the dissolved oxygen meter in real time. After the reading of the dissolved oxygen meter stabilizes (the reading of the dissolved oxygen meter changes by less than 1% within 5 minutes), read the dissolved oxygen reading on the dissolved oxygen meter. 始 .

[0074] Step 2: Detect the final oxygen content of the degassed liquid after degassing. On the basis of step 1, turn on the vacuum equipment to vacuum purge the inner layer of the membrane to degas the degassed liquid. Keep the vacuum reading at -0.094MPa (50torr) during vacuum purge. Observe the changes in the dissolved oxygen reading on the dissolved oxygen meter in real time. When the reading of the dissolved oxygen meter stabilizes (the reading of the dissolved oxygen meter changes by less than 1% within 5 minutes), the degassing is considered to have reached equilibrium. Read the dissolved oxygen reading on the dissolved oxygen meter. 终 The deoxidation efficiency is calculated by the following formula:

[0075] The tensile strength and elongation at break of the degassing membrane can be tested by the following test method: use a stretching machine to uniformly stretch the degassing membrane sample at room temperature (stretching speed is 50mm / min, the distance between the upper and lower clamps is 30mm) until the degassing membrane breaks, so as to measure the tensile strength and elongation at break, repeat 3 times, and take the average value; the average value is the final tensile strength and elongation at break of the membrane. When testing the tensile strength and elongation at break of the degassing membrane, it is usually necessary to control the inner diameter of the degassing membrane to be consistent, for example, control the inner diameter to 0.2mm before conducting the corresponding test.

[0076] Furthermore, the present invention also provides a process for preparing a high-tolerance PMP hollow fiber degassing membrane, comprising the following process steps:

[0077] S1, spinning, the PMP material is melt-extruded in a die head, and a molded product having an inner surface and an outer surface is formed under the action of an inner core, wherein the die head extrusion temperature is 250-280°C;

[0078] S2, air section pre-crystallization, placing the molded product in the air section for pre-crystallization, wherein the temperature of the air section is 30-70°C and the length of the air section is 500-1500mm;

[0079] S3, air cooling crystallization, the molded product obtained in step S2 is cooled by air blowing in a gas atmosphere, wherein the air blowing temperature is 40-70°C and the air blowing speed is 20-50m / min, to obtain nascent fibers;

[0080] S4, first heat setting, subjecting the spun fiber to a first heat setting treatment, the first heat setting temperature is 70-100° C., the first heat setting time is 60-180 min, and a heat set semi-finished product is obtained;

[0081] S5, heat drawing treatment, heat drawing the heat-set semi-finished product to obtain a heat-drawn semi-finished product, wherein the ratio of the heat drawing temperature to the first heat setting temperature is 1.5-3:1, wherein the heat drawing stretching rate is 1-10%, and the heat drawing rate is not less than 0.5 m / min;

[0082] S6, second heat setting, the heat-drawn semi-finished product is subjected to a second heat setting treatment to obtain a hollow fiber membrane.

[0083] Further, in step S1, the weight average molecular weight of the PMP material is 300,000-800,000, and the melt index is 8-15 g / min@(260° C., 5 kg);

[0084] In step S5, the hot-drawing temperature is preferably 160-180°C, the hot-drawing stretching ratio is 2-8%, and the hot-drawing rate is 1 m / min-10 m / min.

[0085] Further, in step S1, an inert gas is used as the inner core, and the flow rate of the inert gas is 2-5 ml / min, wherein the inert gas is nitrogen, helium or argon;

[0086] In step S1, the stretching ratio of the die head is 10-50;

[0087] In step S3, the gas atmosphere is preferably an inert gas, wherein the inert gas is nitrogen, helium or argon, and the winding speed is 100m / min-200m / min.

[0088] Furthermore, in step S6, the ratio of the second heat setting temperature to the first heat setting temperature is 1.1-2:1, and the second heat setting temperature is at least 10°C lower than the hot drawing temperature, preferably 15-60°C lower; the second heat setting time is 2-15 minutes.

[0089] Furthermore, in step S6, a stretching treatment is performed during the second heat setting, the stretching ratio is 0.1%-0.5%, the stretching rate is 1m / min-12m / min, and the stretching rate during the stretching treatment is greater than the stretching rate during the hot drawing treatment.

[0090] In the present invention, the first step is to extrude the PMP material after melting it at an appropriate temperature in the inner core to form a molded product with an inner surface and an outer surface. In the process of extruding the molded product, the temperature of the inner core and the weight-average molecular weight and melt index of the PMP material are closely related to the performance of the molded product. Through the action of appropriate inner core temperature (usually the inner core temperature is related to the die extrusion temperature, and the die extrusion temperature is 250-280°C), appropriate weight-average molecular weight (300,000-800,000) and appropriate melt index (8-15g / min@(260°C, 5kg)), the PMP material has appropriate fluidity after melt extrusion, and then an ideal membrane structure is obtained. Preferably, an inert gas is used as the inner core, and the flow rate of the inert gas is 2-5 ml / min, wherein the inert gas is nitrogen, helium or argon. Combined with a suitable stretching ratio of the die (10-50), the part of the molded product close to the inner surface can have a relatively suitable time for cooling and crystallization compared with the outer surface. At the same time, under the action of the die stretching ratio, the inside of the molded product is subjected to a certain stretching effect, ensuring that the molded product can have a suitable degree of orientation, which is conducive to the final degassing film having a higher degree of crystallinity.

[0091] On this basis, the S2 step of the present invention performs air segment pre-crystallization on the molded product, by controlling the temperature of the air segment to 30-70°C, and the length of the air segment to be controlled within the range of 500-1500mm. The main purpose of the air segment of the present invention is to control the slow cooling of the molded product and increase the crystallization time, thereby increasing the number and size of crystal nuclei formed in the molded product, so that the final degassed film has a relatively high degree of crystallinity; preferably, the temperature of the inert gas serving as the inner core is higher than the ambient temperature of the air segment, and the ratio of the temperature of the inert gas in the air segment to the ambient temperature of the air segment is 1.5-4:1. The temperature of the inert gas in the inner core can be basically regarded as the extrusion temperature of the die head. The temperature in the air section and the ambient temperature of the air section are controlled within a suitable range, thereby giving the inner and outer surfaces of the molded product a cooling rate with a suitable degree of difference, so that the number of crystal nuclei on the inner surface of the molded product can be relatively higher than the number of crystal nuclei on the outer surface of the molded product to a certain extent, and the degree of crystallization of the final inner surface of the degassing membrane can be higher than that of the outer surface to a certain extent, and the degassing membrane can also have suitable mechanical strength; in addition, the gap area ratio of the inner surface can also be relatively higher than the gap area ratio of the outer surface to a certain extent, and the appropriate gap area ratio of the inner surface can also make the degassing membrane have extreme tolerance while having a suitable degassing rate and a higher degassing efficiency.

[0092] Then, the molded product is subjected to air-cooled crystallization, the air temperature is controlled at 40-70°C, the air speed is controlled at 20-50m / min, and the gas atmosphere of air-cooled crystallization can be air, preferably an inert gas, wherein the inert gas is nitrogen, helium or argon; combined with the inner core being an inert gas such as nitrogen and the air section atmosphere, we found that the molded product exposed to an inert gas environment may be more conducive to promoting the conversion of the III crystal form to the I crystal form to a certain extent, and the I crystal form has the lowest crystal region density among the PMP crystal forms, which then makes the crystal region density of the final PMP degassing membrane lower than the density of the amorphous region, giving the PMP degassing membrane good gas permeability. At the same time, the winding speed of the air-cooled crystallization section is controlled at 100m / min-200m / min. Combined with the effect of the length of the air section, it is ensured that the molded product has a suitable air section residence time for pre-crystallization, and it can also have a certain stretching effect on the molded product, which is also conducive to the formation of a certain crack structure on the inner and outer surfaces of the subsequent degassing membrane.

[0093] Next, the spun fiber is subjected to the first heat setting treatment, which is also one of the relatively critical process nodes in the present invention. The study found that when the first heat setting temperature is controlled at a relatively high temperature (controlled at 70-100°C) and the first heat setting time is controlled at 60-180min, it is more conducive to the degassing film having a better crystallinity and a higher degassing efficiency. The R&D personnel analyzed that within a certain temperature range, the higher the temperature of the first heat setting, the more conducive it is to the formation of more and larger crystal nuclei inside the spun fiber, and finally the overall crystallinity of the degassing film remains relatively high, and there are suitable gaps between the formed lattices, so that the gas to be removed can be better degassed through the gaps between the lattices, and finally the degassing efficiency of the degassing film is well improved. At the same time, the time of the first heat setting is also particularly important. When the first heat setting time is controlled at 60-180min, it can ensure to a certain extent that the appropriate number and size of crystal nuclei can be fully formed during the first heat setting process, thereby improving the crystallinity of the degassing film. If the temperature of the first heat setting is low, the size of the crystal nuclei formed in the heat-setting semi-finished product may be relatively small, and the spacing between the crystal lattices may also be affected to a certain extent, thereby affecting the rate at which the degassing membrane can achieve gas penetration through the gaps between the crystal lattices, ultimately manifesting as a relatively poor degassing efficiency of the degassing membrane.

[0094] Next, the heat-set semi-finished product is subjected to a heat-drawing process, which is also the most important process node in the present invention. The heat-set semi-finished product of the present invention is not subjected to a cold-drawing process, but is directly subjected to a heat-drawing process, wherein the ratio of the heat-drawing temperature to the first heat-setting temperature needs to be controlled to be 1.5-3:1, the heat-drawing stretching rate is 1%-10% (preferably 2%-8%), and the heat-drawing rate is not less than 0.5 m / min; after the first heat-setting, the residual stress defects in the heat-set semi-finished product are well eliminated. At this time, the heat-drawing temperature is preferably 16 0-180℃, so that during the hot drawing process, no excessive pore structure will appear in the heat-set semi-finished product, but a relatively dense or certain crack structure will be formed; it should be noted that the hot drawing rate cannot be too slow, and the hot drawing rate is preferably 1m / min-10m / min, so as to avoid the appearance of larger pore structure during the hot drawing process as much as possible. At the same time, under the action of appropriate hot drawing stretching rate, the ideal pore structure can be better formed in the heat-set semi-finished product, such as the formation of a suitable crack structure, etc., avoiding the problem of forming more or larger pore structures due to excessive hot drawing stretching rate. In addition, under the combined effect of controlling the first heat setting temperature at a relatively high temperature (70-100°C) and keeping the ratio of the hot drawing temperature to the first heat setting temperature within an appropriate range (1.5-3:1), we found that on the one hand, the crystallinity of the final degassed film can be increased to a certain extent, and on the other hand, it will be more conducive to the increase of crystal form I in the crystal region. This may be related to the stability of crystal form I itself. Crystal form I is more stable than other crystal forms, and when affected by such an external environment, it will drive the unstable crystal state to transform into a stable crystal state.

[0095] Finally, the heat-drawn semi-finished product is subjected to a second heat setting treatment, the ratio of the second heat setting temperature to the first heat setting temperature is 1.1-2:1, and the second heat setting temperature is at least 10°C lower than the heat drawing temperature, preferably 15-60°C lower; the second heat setting time is 2-15min; the second heat setting process is, on the one hand, to eliminate the residual stress defects in the heat-drawn semi-finished product so as to form a suitable degassing membrane structure; on the other hand, through the coordination of the second heat setting temperature and the heat drawing temperature, the pore structure such as cracks generated during the heat drawing process can be better stabilized to avoid the second heat setting. The temperature is too high and the fusion disappears; in addition, as a preference, a slight stretching treatment can be performed during the second heat setting, with a stretching ratio of 0.1%-0.5%, a stretching rate of 1m / min-12m / min, and the stretching rate during the stretching treatment is greater than the stretching rate during the heat drawing treatment. By performing a faster and slight stretching treatment on the heat-drawn semi-finished product during the second heat setting process, it is more conducive to the final degassing film having a higher degree of crystallinity, and is also conducive to forming an ideal film structure, thereby better improving the degassing rate and degassing efficiency of the degassing film, while the degassing film still has excellent tolerance.

[0096] Furthermore, the present invention also provides an application of a highly tolerant PMP hollow fiber degassing membrane, wherein the hollow fiber degassing membrane is applied to at least one of photoresist filtration degassing, ceramic ink degassing and UV ink degassing; the degassing membrane of the present invention is particularly suitable for liquid systems with certain corrosiveness and active chemical properties or liquid systems with strong permeability, such as ceramic ink degassing, UV ink degassing and PI glue degassing in photoresist, etc. Of course, the degassing membrane of the present invention can also be applied to other degassing application fields.

[0097] In summary, the present invention includes at least one of the following beneficial technical effects:

[0098] 1. The present invention has a relatively high XRD crystallinity and a suitable proportion of crystal type I, so that the degassing membrane has a suitable lattice spacing, a suitable molecular chain arrangement and a crystal area density, so that the gas to be removed can penetrate through the gaps between the lattices. In addition, the PMP material itself has a good selective permeability to O2. Combined with the degassing membrane having a suitable thickness (10-50μm) and a certain O2 permeation rate, the degassing membrane is guaranteed to have a high degassing efficiency, basically replacing the PTFE degassing membrane, and is suitable for use in the degassing field of liquid systems with certain corrosiveness and active chemical properties or liquid systems with strong permeability.

[0099] 2. The present invention enables the degassing membrane to have a better gas permeation rate by providing the first cracks and inner degassing holes of appropriate number and size on the inner surface of the degassing membrane and the second cracks of appropriate number and size on the outer surface of the degassing membrane, thereby being able to better improve the degassing rate and degassing efficiency of the degassing membrane while having better tolerance; in addition, we unexpectedly found that when the inner surface of the degassing membrane has a certain number and size of inner degassing holes and first cracks and the outer surface of the degassing membrane has an appropriate number and size of second cracks, the toughness of the degassing membrane can also be relatively better improved, and the tensile strength and elongation at break of the degassing membrane can be improved to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0100] The present invention will be further described below in conjunction with the accompanying drawings:

[0101] Figure 1 This is a scanning electron microscope image of the inner surface of the hollow fiber degassing membrane prepared in Example 4, where the magnification is 20K×;

[0102] Figure 2 This is a scanning electron microscope image of the outer surface of the hollow fiber degassing membrane prepared in Example 4, wherein the magnification is 10K×;

[0103] Figure 3 This is a scanning electron microscope image of the inner surface of the hollow fiber degassing membrane prepared in Example 5, wherein the magnification is 50K×;

[0104] Figure 4 This is a scanning electron microscope image of the outer surface of the hollow fiber degassing membrane prepared in Example 5, wherein the magnification is 2K×;

[0105] Figure 5 This is a scanning electron microscope image of the outer surface of the hollow fiber degassing membrane prepared in Example 6, wherein the magnification is 50K×;

[0106] Figure 6 This is the XRD diffraction pattern analysis diagram of the hollow fiber degassing membrane prepared in Example 6. DETAILED DESCRIPTION

[0107] The present invention is further described in detail below in conjunction with the examples. Unless otherwise specified, in the following examples, the raw materials and equipment used to prepare the hollow fiber membranes can be purchased through commercial channels.

[0108] Example 1

[0109] A method for preparing a highly tolerant PMP hollow fiber degassing membrane comprises the following steps:

[0110] S1, spinning, melt-extrude the PMP material in the die head, and form a molded product with an inner surface and an outer surface under the action of the inner core, wherein the die head extrusion temperature is 250°C; wherein the weight average molecular weight of the PMP material is 800,000, the melt index is 15g / min@(260°C, 5kg), and an inert gas is used as the inner core, the flow rate of the inert gas is controlled to be 5ml / min, and the die head stretch ratio is 10;

[0111] S2, air section pre-crystallization, the molded product is placed in the air section for pre-crystallization, wherein the temperature of the air section is 30°C and the length of the air section is 500mm;

[0112] S3, air cooling crystallization, the molded product obtained in step S2 is blown and cooled in a gas atmosphere, wherein the blowing temperature is 40° C. and the blowing speed is 50 m / min, to obtain spun fibers, wherein the gas atmosphere is an inert gas and the winding speed is 200 m / min;

[0113] S4, first heat setting, subjecting the spun fiber to a first heat setting treatment, the first heat setting temperature is 70° C., the first heat setting time is 180 min, and a heat set semi-finished product is obtained;

[0114] S5, heat drawing treatment, heat drawing the heat-set semi-finished product to obtain a heat-drawn semi-finished product, wherein the ratio of the heat drawing temperature to the first heat setting temperature is 1.5-3:1, wherein the heat drawing temperature is 155°C, the heat drawing elongation is 1%, and the heat drawing rate is 10 m / min;

[0115] S6, second heat setting, the heat-drawn semi-finished product is subjected to a second heat setting treatment, wherein the second heat setting temperature is 145° C., and the second heat setting time is 15 minutes, to obtain a hollow fiber membrane.

[0116] Embodiment 2-7

[0117] The difference between Example 2-7 and Example 1 lies in the different process parameters, and the specific differences are shown in Table 1-1 and Table 1-2.

[0118] Comparative Example 1

[0119] The difference between Comparative Example 1 and Example 1 is that the process parameters are different, and the specific differences are shown in Table 1-1 and Table 1-2.

[0120] Comparative Example 2

[0121] The difference between Comparative Example 2 and Example 1 is that, instead of hot drawing, cold drawing is performed, wherein the cold drawing temperature is 40° C., and the cold drawing elongation is 30%. The other differences are shown in Table 1-1 and Table 1-2.

[0122] Comparative Example 3

[0123] Comparative Example 3 is a PP hollow fiber degassing membrane with product model HZ6040 of Hangzhou Hengfiltrate Technology Engineering Co., Ltd., in which the PP hollow fiber degassing membrane was subjected to a tolerance test and its tolerance was poor. The membrane fibers were broken through by the isobutanol solution containing methyl orange in no more than 5 minutes.

[0124] Comparative Example 4

[0125] Comparative Example 4 is a PTFE hollow fiber degassing membrane of DIC product model PF-03F, wherein the deoxygenation efficiency of the PTFE hollow fiber degassing membrane was tested, and the deoxygenation efficiency was relatively low, which did not exceed 20%.

[0126] Table 1-1

[0127]

[0128]

[0129] Table 1-2

[0130]

[0131] Membrane structure parameter detection

[0132] The PMP hollow fiber degassing membranes prepared in Example 1-7 and Comparative Example 1-2 were morphologically characterized using a scanning electron microscope (Hitachi S-5500). The outer surface and inner surface of the PMP hollow fiber degassing membrane were selected as observation objects. The specific detection and measurement results are shown in Tables 2-1 and 2-2.

[0133] Table 2-1

[0134]

[0135] Table 2-2

[0136]

[0137] The inner and outer surfaces of the PMP degassing membrane of Comparative Example 2 both form a pore structure, wherein the pore structure on the inner surface is internal degassing pores, and the pore structure on the outer surface is external degassing pores. The internal and external appearances of the PMP degassing membrane of Comparative Example 2 were observed, and the SEM average pore diameter of the internal degassing pores on the inner surface was measured to be 55 nm, and the SEM average pore diameter of the external degassing pores on the outer surface was 18 nm.

[0138] The inner and outer surface morphologies of the PP degassing membranes and PTFE degassing membranes of Comparative Examples 3-4 were measured, and the inner and outer surfaces of the PP degassing membrane of Comparative Example 3 and the PTFE degassing membrane of Comparative Example 4 were both relatively dense.

[0139] Membrane performance parameter detection

[0140] 1.1 Tensile strength and elongation at break test

[0141] After testing, the tensile strength of the PMP hollow fiber degassing membranes prepared in Examples 1-7 is not less than 150CN, and the elongation at break is 30%-150%, that is, they all have large tensile strength and elongation at break, and can meet the needs of industrialization; among them, the tensile strength of the PMP hollow fiber degassing membranes prepared in Examples 3, 4, 5 and 6 is not less than 250CN, and the broken fibers of the PMP hollow fiber degassing membranes during the preparation process and after preparation are significantly reduced, and the membranes have good toughness. It is speculated that this is due to the selection of better process conditions in the preparation process.

[0142] 1.2 Deoxygenation efficiency test; 1.3 Oxygen permeation rate test; 1.4 Tolerance test.

[0143] The test results are shown in Table 3.

[0144] Table 3

[0145]

[0146] From the above, it can be seen that the hollow fiber degassing membranes prepared in Examples 1-7 of the present invention have a high degree of crystallinity and a high proportion of crystal form I. Combined with the PMP material having good stability and oxygen selective permeability, the PMP hollow fiber degassing membrane is used in the degassing field of liquid systems with certain corrosiveness and active chemical properties or liquid systems with strong permeability, such as UV ink degassing, ceramic ink degassing and PI glue degassing in photoresist, etc. The PMP hollow fiber degassing membrane can have excellent tolerance, and at the same time has a good degassing rate and a high degassing efficiency. In addition, the hollow fiber degassing membrane of the present invention also has good toughness. The tensile strength of the PMP hollow fiber degassing membrane is not less than 150CN, and the elongation at break is 30-150%.

[0147] Although the PMP hollow fiber degassing membrane prepared in Comparative Example 1 has good tolerance, its degassing rate and degassing efficiency are poor, which can hardly meet the actual degassing needs; although the degassing rate of the PMP hollow fiber degassing membrane prepared in Comparative Example 2 is good, its tolerance and degassing efficiency are poor, which can hardly meet the degassing needs of liquid systems with certain corrosiveness and active chemical properties or liquid systems with strong permeability, such as UV ink degassing, ceramic ink degassing and PI glue degassing in photoresist; the PP degassing membrane prepared in Comparative Example 3 has poor tolerance when applied to the degassing field of liquid systems with certain corrosiveness and active chemical properties or liquid systems with strong permeability, and cannot meet the degassing needs in the above-mentioned degassing fields; when the PTFE degassing membrane prepared in Comparative Example 4 is applied to the degassing field of liquid systems with certain corrosiveness and active chemical properties or liquid systems with strong permeability, although its tolerance is excellent, its degassing efficiency is low, which can hardly meet the degassing needs in the above-mentioned degassing fields, and the economic benefits are poor.

[0148] The preferred embodiments of the present invention have been described in detail above, but it should be understood that after reading the above teachings of the present invention, those skilled in the art may make various changes or modifications to the present invention. These equivalent forms also fall within the scope defined by the appended claims of the present invention.

Claims

1. A high-tolerance PMP hollow fiber degassing membrane, comprising a main body, one side of the main body is an inner surface facing the inner cavity, the other side of the main body is an outer surface, and the main body has a non-directional tortuous channel, characterized in that: The thickness of the degassing film is 10-50 μm; The O2 permeation rate of the degassing membrane is 10-100 ml / (min·bar·m 2 ); The XRD crystallinity of the degassing film is not less than 60%; The degassing film contains crystal form I belonging to the tetragonal system, wherein the content of crystal form I accounts for 60%-98.5% of the overall crystal form; Under the action of an inlet pressure of 0.5 MPa, an isobutyl alcohol solution containing methyl orange was used as a standard solution to fill the outer surface of the hollow fiber degassing membrane, and a breakthrough time test was performed on the hollow fiber degassing membrane. The breakthrough time of the hollow fiber degassing membrane was greater than 60 min.

2. A high-tolerance PMP hollow fiber degassing membrane according to claim 1, characterized in that: The thickness of the degassing film is 12-45 μm; the gap area ratio of the outer surface is not higher than 2%; the gap area ratio of the inner surface is not higher than 10%, and the gap area ratio of the inner surface is greater than the gap area ratio of the outer surface; The O2 permeation rate of the degassing membrane is 20-90 ml / (min·bar·m 2 ); The XRD crystallinity of the degassing film is 70%-90%.

3. A high-tolerance PMP hollow fiber degassing membrane according to claim 1, characterized in that: The diffraction peak intensity of the degassing film near 9.5° at 2θ angle in the XRD diffraction spectrum accounts for 60%-90% of the overall crystal diffraction peak intensity, the half-peak width of the diffraction peak near 9.5° at 2θ angle is 0.1°-0.5°, and the grain size is not less than 200 angstroms.

4. A high-tolerance PMP hollow fiber degassing membrane according to claim 1, characterized in that: The inner surface has a plurality of first cracks in the form of silver streaks, and the average SEM width of the first cracks is 0.1-20 nm; The content of the Form I crystal accounts for 70%-98% of the overall crystal form.

5. A high-tolerance PMP hollow fiber degassing membrane according to claim 4, characterized in that: A plurality of the first cracks are evenly distributed on the inner surface, the SEM average width of the first cracks is 1-18 nm, and the gap area ratio of the inner surface is 0.2%-8%.

6. A high-tolerance PMP hollow fiber degassing membrane according to claim 4, characterized in that: The inner surface has an inner crack zone and an inner dense zone, the inner dense zone is a dense area, a number of the first cracks are located in the inner crack zone, and the SEM average width of the first cracks is 0.5-15nm, and the gap area rate of the inner crack zone is 0.5%-9%.

7. A high-tolerance PMP hollow fiber degassing membrane according to claim 1, characterized in that: The inner surface has a plurality of inner degassing pores, the SEM average pore size of the inner degassing pores is greater than the SEM average width of the first cracks, the SEM average pore size of the inner degassing pores is 1-40 nm, and the thickness of the degassing film is 18-48 μm.

8. A high-tolerance PMP hollow fiber degassing membrane according to claim 7, characterized in that: The density of the inner degassing pores is not more than 20 / 1 μm 2 , the ratio of the SEM average pore size of the inner degassing pores to the SEM average width of the first cracks is 1.5-15.

9. A high-tolerance PMP hollow fiber degassing membrane according to claim 4, characterized in that: The outer surface is provided with a plurality of second cracks, the SEM average width of the second cracks is no more than 20 nm, and the ratio of the SEM average width of the second cracks to the SEM average width of the first cracks is 0.2-0.

9.

10. A high-tolerance PMP hollow fiber degassing membrane according to claim 1, characterized in that: The infrared absorption spectra of the inner and outer surfaces of the degassing film are tested by the ATR method, and the orientation coefficient X of the degassing film is calculated; X=ABS 918 / ABS 1465 ; ABS 918 For degassing membrane, the wave number is 918 cm -1 The absorption intensity in the vicinity; ABS 1465 For degassing membrane, the wave number is 1465cm -1 The absorption intensity in the vicinity; The external surface orientation coefficient X 外 =ABS 外表面918 / ABS 外表面1465 ; Where X 外 The value range is 0.005-0.18; ABS 外表面918 The outer surface of the degassing membrane is at a wave number of 918 cm -1 The absorption intensity in the vicinity; ABS 外表面1465 The outer surface of the degassing membrane at a wave number of 1465 cm -1 The absorption intensity near 11. A high-tolerance PMP hollow fiber degassing membrane according to claim 1, characterized in that: The inner surface orientation coefficient X 内 =ABS 内表面918 / ABS 内表面1465 ; Where X 内 The value range is 0.01-0.2; and X 内 :X 外 Meets 1.01-5; ABS 内表面918 The outer surface of the degassing membrane is at a wave number of 918 cm -1 The absorption intensity in the vicinity; ABS 内表面1465 The outer surface of the degassing membrane at a wave number of 1465 cm -1 The absorption intensity near 12. A high-tolerance PMP hollow fiber degassing membrane according to claim 1, characterized in that: The tensile strength of the degassing film is not less than 150CN, and the elongation at break is 30-150%; The deoxidation efficiency of the degassing membrane is 25%-70%.

13. A method for preparing a high-tolerance PMP hollow fiber degassing membrane according to any one of claims 1 to 12, characterized in that: The process steps include: S1, spinning, the PMP material is melt-extruded in a die head, and a molded product having an inner surface and an outer surface is formed under the action of an inner core, wherein the die head extrusion temperature is 250-280°C; S2, air section pre-crystallization, placing the molded product in the air section for pre-crystallization, wherein the temperature of the air section is 30-70°C and the length of the air section is 500-1500mm; S3, air cooling crystallization, the molded product obtained in step S2 is cooled by air blowing in a gas atmosphere, wherein the air blowing temperature is 40-70°C and the air blowing speed is 20-50m / min, to obtain nascent fibers; S4, first heat setting, subjecting the spun fiber to a first heat setting treatment, the first heat setting temperature is 70-100° C., the first heat setting time is 60-180 min, and a heat set semi-finished product is obtained; S5, heat drawing treatment, heat drawing the heat-set semi-finished product to obtain a heat-drawn semi-finished product, wherein the ratio of the heat drawing temperature to the first heat setting temperature is 1.5-3:1, wherein the heat drawing stretching rate is 1-10%, and the heat drawing rate is not less than 0.5 m / min; S6, second heat setting, the heat-drawn semi-finished product is subjected to a second heat setting treatment to obtain a hollow fiber membrane.

14. The method for preparing a high-tolerance PMP hollow fiber degassing membrane according to claim 13, characterized in that: In step S1, the weight average molecular weight of the PMP material is 300,000-800,000, and the melt index is 8-15 g / min@(260° C., 5 kg); In step S5, the hot-drawing temperature is preferably 160-180°C, the hot-drawing stretching ratio is 2-8%, and the hot-drawing rate is 1 m / min-10 m / min.

15. The method for preparing a high-tolerance PMP hollow fiber degassing membrane according to claim 13, characterized in that: In step S1, an inert gas is used as the inner core, and the flow rate of the inert gas is 2-5 ml / min, wherein the inert gas is nitrogen, helium or argon; In step S1, the stretching ratio of the die head is 10-50; In step S3, the gas atmosphere is preferably an inert gas, wherein the inert gas is nitrogen, helium or argon, and the winding speed is 100m / min-200m / min.

16. The method for preparing a high-tolerance PMP hollow fiber degassing membrane according to claim 13, characterized in that: In step S6, the ratio of the second heat setting temperature to the first heat setting temperature is 1.1-2:1, and the second heat setting temperature is at least 10°C lower than the hot drawing temperature, preferably 15-60°C lower; the second heat setting time is 2-15 minutes.

17. The method for preparing a high-tolerance PMP hollow fiber degassing membrane according to claim 13, characterized in that: In step S6, a stretching treatment is performed during the second heat setting, the stretching ratio is 0.1%-0.5%, the stretching rate is 1m / min-12m / min, and the stretching rate during the stretching treatment is greater than the stretching rate during the heat drawing treatment.

18. The use of a high-tolerance PMP hollow fiber degassing membrane according to any one of claims 1 to 12, characterized in that: The degassing membrane is applied to at least one of photoresist filtration degassing, ceramic ink degassing and UV ink degassing.

Citation Information

Patent Citations

  • Ammonia-nitrogen wastewater treatment system and process based on PTFE (polytetrafluoroethylene) deamination membrane component

    CN106045175A

  • Porous polypropylene hollow filaments and method making the same

    US4055696A

Cited By

  • A polytetrafluoroethylene composite degassing membrane and a roll-to-roll continuous coating modification forming process thereof

    CN122702335A